Monumental entrances at iberian Neolithic and Chalcolithic ditches enclosures. Entrance 1 at Perdigoes (Portugal) as case study - Caro-Herrero, José Luis; Márquez-Romero, José Enrique; Jiménez-Jáimez, Víctor José (My University, 2015)
Ditched enclosures have been found in many European regions during the Neolithic and Copper Age. This widespread, almost pan-European monumental tradition has also been documented in the Iberian Peninsula in the last 25 years, although the impact of their discovery in the continental debates has been, for the most part, rather small. In these enclosed sites, ditches delimit spaces by establishing an inside and an outside. Crucially, however, in most enclosures known to date with enough detail, ditches show one or more interruptions interpreted as entrances or points of access that connect the outside with the inside. These entrances appear to be architectural elements of great importance and possibly special meanings. During the Neolithic, European ditched enclosures showed great formal variability, from the simplest (a break or discontinuity in the ditch's layout) to more complex forms such as the pince de crabe (crab's claw). Many of them show astrological awareness and/or orientation towards certain prominent features of the surrounding landscape. Changes in form and transformations through time, both of the entrance itself and of the nearby elements, are also very common. All in all, they are an important component of almost every ditched enclosure, and often some of the most visibly monumentalised areas of these sites. This presentation has two objectives. First, we shall examine the monumental character and the diversity of entrances at Southern Iberian Neolithic and Chalcolithic ditched enclosures (4th-3rd millennia cal BC). Second, we will focus on Entrance 1 at Perdigões (Portugal), its form, features and temporality, as a particular case to be contextualised in the wider Southern Iberian scene.
Keywords: Prehistoria; 3D; Prehistory; Enclosures